Holy, holy, holy : the story of a liturgical formula - Williamson, H. G. M. (Hugh Godfrey Maturin), 1947- (Julius-Wellhausen-Vorlesung., 2008)
In one form or another, the Trisagion,?Holy, holy, holy is the Lord of hosts; the whole earth is full of his glory?, entered Jewish and Christian liturgy at an early stage from Isaiah?s account of his vision as recorded in Isaiah 6. Before that happened, however, it is likely that it went through a significant change of meaning from what the Old Testament prophet himself meant by it. Drawing on material that was familiar to him from the worship of the Jerusalem temple, he used it distinctly but characteristically to challenge his audience?s view that God would automatically protect them from.